Influence of Society Changes on the Model of Hazardous Goods Road Transportation - Muha, Robert; Sever, Drago (Promet - Traffic&Transportation, 2012)
The transportation of hazardous goods represents an economic activity whose consequences can have serious impact on the safety of transportation, the environment and human health. With the aim of reviewing the elements that affect the activity, this article presents a model for the transportation of hazardous goods of which, generally, there are two forms: the theoretical model for the transportation of hazardous goods, which represents the goal for the establishment of relations on the transportation of hazardous goods services market; and the real model for the transportation of hazardous goods, which represents an adaptation of the theoretical model to the status in a specific localised region. The research, which was conducted as part of the principal author’s Ph.D. thesis, illustrates the exceptional influence of the society changes within a specific country. The theoretical model for the road transportation of hazardous goods is transposed into the real transportation services environment in Slovenia and it presents its transition and incorporation into the common EU transportation service market.KEY WORDS: transportation policy, model of the road transportation of hazardous goods